Influence of ultrasound and template on the properties of nickel hydroxide as an active substance of supercapacitors - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2018)
Nickel hydroxide is widely used as an active materials of supercapacitors. The most active are Ni(OH)2 (α+β) samples with layered structure synthesized in a slit-diaphragm electrolyzer. The study on the influence of template synthesis and ultrasound treatment on the characteristics of the samples was conducted. The synthesis of nickel hydroxide samples in the presence of polyvinyl alcohol as a template and the use of ultrasound treatment of the Ni(OH)2 suspension directly after formation was carried out. The synthesized samples of nickel hydroxide were studied by means X-ray diffraction analysis, scanning electron microscopy, and BET nitrogen adsorption-desorption. Electrochemical characteristics were evaluated by means of galvanostatic charge-discharge cycling in the supercapacitor regime. Comparative analysis of the Ni(OH)2 sample has revealed both negative and positive effect of the template and ultrasound. The use of PVA as a template and ultrasound treatment resulted in a significant decrease in specific surface area (to 6 m2/g) and an increase of the average pore diameter (to 1181 Ǻ). Application of the template and ultrasound decreases crystallinity and increases the content of α-form, which results in the increased capacity of the samples. The maximum value of 233 F/g is achieved at a current density of 40 mA/cm2 obtained from the combined effect of the template and ultrasound. Under these conditions, the specific capacity of the sample prepared without the template and ultrasound is 76 F/g. However, with an increase of current density to 120 mA/cm2, the capacity of this sample increases to 303 F/g. At the same time, for samples synthesized with the template and ultrasound, a decrease of capacity is observed at higher current densities, which is related to difficulties in the breakdown of agglomerated particles. In case of the introduced template, this is explained by the binding effect of the remaining PVA and in case of ultrasound treatment – particle condensation. Based on the results of the comparative analysis, it is recommended to replace the template with a more easily removable one and also conduct an electrochemical synthesis of Ni(OH)2 in SDE directly in the ultrasound field and increase the power of the emitter.